States Taking the Reins? Employment Verification Requirements and Local Labor Market Outcomes - Shalise Ayromloo; Benjamin Feigenberg; Darren Lubotsky (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
We estimate the impact of state-level -Verify" legislation that mandates employment eligibility verification for private-sector workers. We document declines in formal sector employment and employment turnover after mandate passage, with e ects concentrated among those likeliest to be work-ineligible. Using newly available data, we show that larger firms are far more likely to comply with mandates. Heterogeneity in adherence leads to substantial within-state employment spillovers from larger to smaller firms, as well as a reduction in the number of large firms. We find no evidence that work-ineligible populations relocate or that native-born workers' labor market outcomes improve in response to mandates.
Keywords: 330